Utilization Of Social Media As A Means Of Socialization To Prevent The Spread Of Covid-19 In The Youth Community In The Kudus District - Munawar Kholil (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The lack of understanding of the public in Kudus Regency regarding preventing the spread of Covid-19 makes people continue their activities as usual without following the health protocols that have been published in the Kudus Regent Circular. Many young people do activities outside the home, such as in coffee shops or hanging out in public spaces, ignoring physical distancing and not wearing masks. The existence of these conditions requires an increase in understanding for youth about the importance of preventing the spread of Covid-19 by utilizing social media. The methods used in this activity are collecting material, making videos / images for social media, editing videos and images, and uploading these videos on various social media such as YouTube and Instagram TV, while images are uploaded on Instagram and Twitter. The output of this activity is an increase in the understanding of young people about preventing the spread of Covid-19, so as to minimize the spread of Covid-19 in Kudus Regency.